2022
DOI: 10.1002/rhc3.12262
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic publishing: A bibliometric review of COVID‐19 research in the crisis and disaster literature

Abstract: Iconic events have traditionally instigated progression in the fields of crisis and disaster science. In the wake of the COVID-19 pandemic, the pressing question is how this global health emergency impacted the research agendas of our field. We reviewed contributions in ten important crisis and disaster journals in the two and a half years following the COVID-19 outbreak from 1 January 2020 to 30 June 2022. Specifically, we conducted a bibliometric review using thematic mapping analysis to distill the major th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…In the aftermath of the COVID‐19 pandemic, we expect to see increased research on instructive communication aimed at influencing behavior and promoting compliance with necessary measures. In our editorial review on “Pandemic publishing” (Kuipers et al, 2022), we saw that “crisis communication” as a theme gained a strong internal coherence or high density (studies share many keywords within the theme). The main subthemes were a new focus on the vulnerability and resilience of specific minorities and communities, the influence of crisis communication on citizen behavior, and the relation between crisis communication and business or economic performance.…”
Section: Discussionmentioning
confidence: 97%
“…In the aftermath of the COVID‐19 pandemic, we expect to see increased research on instructive communication aimed at influencing behavior and promoting compliance with necessary measures. In our editorial review on “Pandemic publishing” (Kuipers et al, 2022), we saw that “crisis communication” as a theme gained a strong internal coherence or high density (studies share many keywords within the theme). The main subthemes were a new focus on the vulnerability and resilience of specific minorities and communities, the influence of crisis communication on citizen behavior, and the relation between crisis communication and business or economic performance.…”
Section: Discussionmentioning
confidence: 97%
“…COVID-19 forced individuals and communities to make difficult choices, often cutting people off from each other [11]; in many cases, this was devastating to community bonds, and weakened human relationships and the ability of people to work together to solve problems. A literature review on COVID-19 in disaster/crisis literature suggested that resilience studies "discuss the necessity of developing dynamic capabilities in logistics and production capacity, recalibrating and reconfiguring operations, as well as the importance of emotions as an intrinsic element of resilience during pandemic governance" [38]. Vasilescu, Apostu, Militaru, and Hysa [39] noted that the COVID-19 response in certain respects showed low resilience, with opportunities available to improve responses for future events.…”
Section: The Impact Of the Covid-19 Pandemicmentioning
confidence: 99%
“…Vasilescu, Apostu, Militaru, and Hysa [39] noted that the COVID-19 response in certain respects showed low resilience, with opportunities available to improve responses for future events. Mental health, clarity of communication, and social responsibility are subtopics associated with community resilience [38].…”
Section: The Impact Of the Covid-19 Pandemicmentioning
confidence: 99%
“…They had overlooked the extent of transboundary crisis management capacities that were required to secure long-term response efforts. Interestingly, when writing our review of pandemic publishing (Kuipers et al, 2022), we noted a similar absence for more generic preparedness in research on epidemics and pandemics, as public health scholars were inclined to focus more on the particularities of specific diseases.…”
mentioning
confidence: 99%